RISK-BASED INSPECTION OF CRUDE AND REFINED OIL STORAGE TANK IN INDONESIA REFINERY PLANT - Sulistomo, Try Rahadi; Surjosatyo , Adi (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2023)
A storage tank, which is used to store oil, is important and high-risk equipment that requires attention to its safety aspects. As a preventive measure, the government requires inspections of all storage tanks, either on a regular basis (every four years) or based on risk assessment. This safety study aims to create an inspection plan for the storage tanks at the oil refinery using the risk-based inspection (RBI) method. The RBI method in this study adopts API RP 581, Third Edition, 2016. Risk analysis is carried out in stages, including collecting technical data on the tanks, determining failure mechanisms, conducting risk analysis, and finally creating an inspection interval and method. Technical data was collected and studied for 29 storage tanks designed according to the API 650 standard. The determined failure mechanisms for the storage tank shell are atmospheric corrosion, general corrosion, and corrosion under insulation. The results of the risk analysis showed that all tanks have a medium risk, with 16 units in category 3C and 13 units in category 2C. The planned inspection methods are visual inspection, UT thickness or flaw thickness, and CUI, with most inspection intervals reaching 10 years. Based on this study, it is concluded that risk-based inspection (RBI) is more effective and efficient than the specific time interval inspection method (every 4 years).